SUMBANGAN APLIKASI TIK TOK BAGI PERKEMBANGAN IMAN MAHASISWA DI RUMAH BINA KARYA ILAHI MADIUN - Tambun, Dheo Elovani; Supriyadi, Agustinus (CREDENDUM: Jurnal Pendidikan Agama, 2023)
Current technological devlopments are one of the driving forces for humans to start transforming from traditional ways of life to modern ones. The development of the media is indeed very necessary for innovations that provide positive benefits for life. The development of information media changes in life, one of which is the life of faith. The Tik Tok application is a trending music video platform network and is popular wih many people, through Tik Tok users are called upon to give testimony to the life of faith as relevant in the Bible. The purpose of this study is to describe what is meant by the Tik Tok application, what is faith that develops and the Tik Tok application has a contribution to the development of student faith at the Formation House Karya Ilahi of Madiun. This study uses a qualitative approach. Data collection techniques through in-dept interviews. The responden of this study were students who lived in the Formation House Karya Ilahi of Madiun. Respondents in this study amounted to (10) people. The results of the study show that respondents understand enough that the Tik Tok application has a contribution to the development of faith because they can spread faith with their own videos.